Does the Integrated Learning Course Affect Openness Traits in Students? - Aka, Kukuh Andri; Wicaksono, Awan; Afandi, ‘Alia Nur Husna (Journal of Educational, Health and Community Psychology, 2025)
This study investigates the impact of integrated learning courses on the development of the openness personality trait among students enrolled in the Elementary School Teacher Education program at the University of Nusantara PGRI Kediri. Adopting a comparative quantitative design, the research compared the openness levels of students who had participated in integrated learning courses with those who had not. Openness was measured using the International Personality Item Pool (IPIP)-BFM-50, focusing on 10 specific indicators. The validity of the items was confirmed through Pearson product-moment correlation (p < .05), and the scale demonstrated acceptable internal consistency (Cronbach’s alpha = .714). Data analysis confirmed the assumptions of normality and homogeneity. Results revealed that students exposed to the integrated learning course scored significantly higher on openness (t(79) = 3.064, p = .003, Cohen’s d = .681), indicating a moderate to large effect size. The study concludes that integrated learning effectively fosters openness—an essential trait for adaptability and cognitive flexibility in 21st-century education. It recommends the broader integration of such courses into teacher education curricula. For future research, a mixed-methods approach is suggested to better understand the underlying processes through which integrated learning influences personality development. Keywords: Integrated learning, openness trait, big five factor